Correlations between Aggression and Explosive Force of Adolescents in the North-Eastern Part of Romania - M.A. Coteata; D.G. Iacob (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The study aims to test the correlation between aggressiveness, evaluated with 2D:4D test, and the explosive force of 45 adolescents aged 15-19 years. The 2D:4D ratio has been determined, as well as the height of squat jump (SJ), countermovement jump (CMJ) and CMJ with arm swing (CMJ-AS), using Just Jump. Correlations were found between the ratio of the two hands, both among girls (p=0.003) and boys (p=0.002). Compared to girls, boys had strong connections between the 2D:4D of the right hand with SJ (p=0.008), CMJ (p=0.006), CMJ-AS (p=0.012) and the average height of the 4 consecutive jumps (p=0.016). Our hypothesis is confirmed, and there are correlations between 2D:4D ratios of both hands and jumps protocols.